A case of brucellosis concomitant with HIV infection in China - Shuai-Bing Dong; Li-Ping Wang; Chao-Xue Wu; Fan Li; Yong Yue; Dong-Ri Piao; Hong-Yan Zhao; Hai Jiang (BMC, 2020)
Abstract Background Human brucellosis is a neglected public health issue in China and reports of HIV-infected individuals complicated with brucellosis are rare. This report describes the case of an HIV-infected patient complicated with brucellosis. We want to raise awareness of clinical diagnosis of brucellosis among clinicians. Furthermore, we should be more concerned about cases with pyrexia of unknown origin, especially in non-epidemic areas of brucellosis in China. Case presentation We encountered the case of a 31-year-old HIV-infected male with a CD4+ T lymphocyte count of approximately 300. On May 1, 2019, the patient had onset of non-specific caustic irregular fever with body temperature reaching 41.0 °C. He was admitted to two medical institutions in Yunnan with pyrexia of unknown origin. Finally, on day 7 of hospitalization in the Public Health Clinical Medical Center in Chengdu City, he was diagnosed as having brucellosis infection based on blood culture results. Conclusions This is the first reported case of brucellosis concomitant with HIV infection in China. Laboratories in infectious disease hospitals and category A level III hospitals in the southern provinces of China should be equipped with reagents for clinical diagnosis of brucellosis and to strengthen the awareness of brucellosis diagnosis in China. Secondly, in provinces with a high incidence of AIDS and brucellosis such as Xinjiang and Henan, it is recommended to implement a joint examination strategy to ensure the early detection, diagnosis, and treatment of this infection.